Vaccinium spp.: Karyotypic and phylogenetic characteristics, nutritional composition, edaphoclimatic conditions, biotic factors and beneficial microorganisms in the rhizosphere - Meléndez-Jácome, María Raquel (2021)
Genus Vaccinium groups plants like shrubs that grows in the highlands of the Andes Mountains. Its fruits are characterized by their antioxidant and nutritional properties. The objective of this paper review was to understand the effect of endophytic and associated microorganisms with the rhizosphere of Vaccinium spp. Wild Vacciunium species present low genetic variability, in comparison with cultivated species that present high variability. Therefore, wild species must be domesticated in order to achieve permanent production in various locations along the year. Domestication of this plant could be achieved by stablishing physiological plant system, determining its edaphoclimatic requirements and analysis of interactions with the plant. One of the main problems of the Vaccinium genus is fungal diseases, such as Botrytis sp. and Hemileia vastatrix. However, other endophytic and rhizosphere microorganisms interact positively with Vaccinium plants: providing mineral nutrients, offering protection against diseases, and even improving soil structure. The diversity of microbiome associated with the plant rhizosphere and the genetic diversity of Vaccinium floribundum are relevant aspects that should be studied to stablish genetic improvement programs and achieve the commercial cropping of the species.